Personal exposure to air pollution in office workers in Ireland: measurement, analysis and implications - Gill, Laurence; Broderick, Brian (My University, 2013)
An experimental assessment of personal exposure to PM10 in 59 office workers was carried out in Dublin; Ireland. Two hundred and fifty five samples of 24 hour personal exposure were collected in real time over a 28 month period. The investigation included an assessment of the uptake of pollutants in the lungs during various daily activities using a Human Respiratory Tract Model. The results of the investigation showed that indoor air quality was the overriding determinant of average daily personal exposure as participants in the study spent over 92% of their time indoors. Exposure in the workplace and exposure at home were the most important microenvironments in total uptake of particulate matter. Exposure while commuting or shopping were found to play a minor role in comparison. The investigation highlighted the importance of considering pollutant uptake as well as personal exposure among receptors where variations in levels of physical activity and duration of exposure are present.
PUBLISHED
Keywords: Air pollution; PM10; Personal exposure; Activity patterns; Uptake; Indoor air quality; Smart & Sustainable Planet